1984
DOI: 10.1063/1.864687
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of ion acoustic waves by the plasma sheath

Abstract: The reflection coefficient R for linear monochromatic ion acoustic waves incident on the transonic layer and sheath from the plasma interior is calculated. The treatment differs from previous analyses in that (1) the exact zero-order ion density and velocity profiles for a planar, bounded plasma are used, and the zero-order charge separation is not neglected, and (2) the first-order quantities near the transonic layer are considered in detail, including first-order charge separation, whereby it is found that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Kuehl investigated theoretically the reflection of ion acoustic soliton, and showed that a shelf develops behind the soliton and the reflected wave is small compared with both trailing shelf and soliton amplitude decrease due to energy transfer to the shelf [17][18][19]. Then after, many authors took the problem of soliton propagation in inhomogeneous plasma in different physical situations like plasma with finite ion temperature [20,21], with negative ions [22][23][24][25], with dust [26] and trapped electrons [27], in magnetic field [28,29], with non isothermal electrons [30], with ionization [31,32], with electron inertia contribution [33] and also in other contexts [16,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Kuehl investigated theoretically the reflection of ion acoustic soliton, and showed that a shelf develops behind the soliton and the reflected wave is small compared with both trailing shelf and soliton amplitude decrease due to energy transfer to the shelf [17][18][19]. Then after, many authors took the problem of soliton propagation in inhomogeneous plasma in different physical situations like plasma with finite ion temperature [20,21], with negative ions [22][23][24][25], with dust [26] and trapped electrons [27], in magnetic field [28,29], with non isothermal electrons [30], with ionization [31,32], with electron inertia contribution [33] and also in other contexts [16,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Other works also suggest that ion-acoustic waves reflect from sheaths. [37][38][39][40] Recently, Hood et al 22 measured fluctuations in an ion presheath at conditions where ion-acoustic instabilities were expected to be excited near the sheath edge. The measurements showed evidence of ion-acoustic fluctuations near the sheath edge, but also further into the plasma in the region predicted by linear theory to be stable 22 .…”
Section: B Ion-acoustic Instabilitiesmentioning
confidence: 99%